Foundation Failures Mitigation under Expansive Clay by Using Granular Pile Anchor System - SFoog, Ehab Hamad; Siang, Alvin John Lim Meng; Naji, Nahla; Sim, Sy Yi; Guntor, Nickholas Anting (International Journal of Integrated Engineering, 2020)
Expansive soils are found in typical areas in the world especially in arid and semi-arid regions. The problems associated with this type of soil drive geotechnical engineers to invent new technologies as remediation’s such as physical and chemical treatments. Innovative foundation techniques were also suggested for remedying the swell-shrink problems of the expansive soil. The granular pile anchor (GPA) is relatively a more favorable technique indebted to its cost-effective, easy and fast to assemble and most importantly was found to be more efficient in remedying the expansive soil. Despite the extensive studies on the expansive soil remedies, yet the granular pile anchor system requires more comprehensive and in-depth investigations. This study is aimed at developing a model with granular piles of various length and diameter extended to the stable zone to investigate the heave and uplift pressure in the expansive soil. For this purpose, experimental and numerical analysis were conducted in a small and in a full scale model respectively. A significant improvement was attained in heave reduction and an increment of uplift capacity. The findings also show that heave decreased significantly when the length and diameter of the GPA increases while the uplift capacity increased. However, it was noted that the extension of length to the stable zone resulted in insignificant changes. Therefore, it can be concluded that the maximum length of 6 m is the ideal length for GPA for this particular type of soil.